New psychoactive substances abuse and its clinical consequences - the case report - Kościuk, Andrzej; Kos, Michał; Drankowska, Justyna; Kaleta, Marcelina; Marzęda, Paweł; Tchórz, Michał (Journal of Education, Health and Sport, 2019)
Introduction: The meteoric rise of new psychoactive substances' use has been a public health problem for at least few years. Their presence was noticed by EU authorities around 2005. First cases of NPS poisoning in Poland appeared shortly thereafter, in 2008. Due to great variety of used substances and lack of information about them, precise diagnosis and targeted treatment remain a significant problem. Hereby, we present a patient with multi-drug poisoning related to NPS abuse and discuss new psychoactive substances that are often found in such cases.Aim of study: To discuss most common new psychoactive substances and their health effects on the basis of the case reportResults: A 28-year old patient was admitted to the Department of Toxicology and Cardiology with symptoms suggesting acute intoxication with psychoactive substances. The patient had a history of drug abuse. A few pouches containing unidentified psychoactive substances were found near the patient. On admission, his condition was serious- he was unconscious and required mechanical ventilation. Tachycardia and aspiration pneumonia were present as well.The applied therapy focused on restoring acid- base homeostasis, electrolyte balance and mitigating toxic influence of detected drugs, with preventive antibiotic administration used as well. His general and psychological condition improved with treatment, and he was discharged from the department after ten days, with continuation of the therapy in ambulatory setting.Conclusions: An increasing amount of patients present cases of polysubstance abuse, whose treatment may prove especially difficult. Such cases require extensive therapy to prevent debilitating complications. A focus on drug regulation and patient education could diminish the number of such cases in the future.